(untitled) (Research, Society and Development, 2023)
Eugenia calycina Cambess. (Myrtaceae) is a fruit species native to Brazil indicated for the recovery of degraded areas. Generally its propagation occurs by seeds, but leads to an increase in the juvenile period of the plants, problems in maintaining seed viability and pathogen incidence. However, with the application of tissue culture techniques it is possible to produce seedlings in large scale, uniformity of the plants obtained and reduction in the period of seed germination. Thus, the objective of this research was to define the best medium for in vitro multiplication of E. calycina. Nodal segments of 1 cm, extracted from E. calycina plants already established in vitro, were used as explants. The treatments consisted of different concentrations of BAP (0; 0.5; 1 and 2 mg L-1) and NAA (0; 0.5; 1 and 2 mg L-1). The experimental design was completely randomized, in a 4x4 factorial scheme, with four concentrations of BAP and four concentrations of NAA, with four replications and three tubes per replication. After 90 days, shoot number, length and fresh mass of the aerial part, production and fresh mass of callus were evaluated. The MS medium plus 2.0 mg L-1 of BAP is ideal for in vitro multiplication of E. calycina.